Comparison Analysis of Peer-to-Peer Lending Performance During COVID-19 Activity Restrictions in Indonesia - Robby Farhan, Abdul; Rokhim, Rofikoh (Dinasti Publisher, 2024)
In recent years the peer-to-peer lending industry has been popular and growing in Indonesia, however activity restrictions due to Covid 19 had an impact on the global economy, especially on financial institutions including peer-to-peer lending. The Indonesian government has determined activity restrictions due to Covid-19 in March 2020 and activity restrictions will be lifted in December 2023. Researchers conducted an analysis to see the stability of peer-to-peer lending by comparing performance data of peer-to-peer lending companies through loan default and the number of loan distributions in the period before, during and after there were no restrictions on Covid 19 activities. The sample in this study used a purposive sampling technique of 72 samples of monthly peer-to-peer lending statistical data that had been registered and supervised by Otoritas Jasa Keuangan in 2018-2023, research was conducted using the General Linear Model Repeated Measure Test and the Friedman Test to determine whether there were significant differences between the three groups, namely the period before, during and after there were no restrictions on Covid 19 activities. The results of the analysis showed that there were significant differences in the loan default statistical values between the group before and during restrictions, the group after and during the Covid 19 pandemic restrictions with p values respectively 0.012 and 0.005. The average amount of loan disbursement has increased every year, but it was found that there was no significant difference between conditions before and during the Covid-19 pandemic restrictions.